2017
DOI: 10.1002/ajoc.201700357
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Iodine‐Promoted Transimination for the Synthesis of 6‐Phenylpyrido[2′,1′:2,3]imidazo[4,5‐c]quinoline and 6‐(Pyridin‐2‐yl)pyrido[2′,1′:2,3]imidazo[4,5‐c]quinolines

Abstract: An unprecedented,e fficient I 2 -mediated approach for the synthesis of 6-phenylpyrido[2',1':2,3]imidazo[4,5c]quinoline heterocyclic skeletons has been achieved from the reaction of benzylamines and 2-(imidazo[1,2-a]pyridin-2yl)anilines. This one-pot protocol proceeds through an oxidation/transimination/cyclization/aromatization reaction sequence under metal-free conditions to result in the formation of NÀCa nd CÀCb onds. Av ariety of benzylamines,i n-cluding pyridin-2-ylmethanamine, were successfully employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 79 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…This is may be due to the strong electron withdrawing nature of the pyridine ring which made the methylene proton para to it so acidic that it took part in the cyclization. Literature study showed only a few reports to synthesize this kind of fused heterocycle.…”
Section: Resultsmentioning
confidence: 99%
“…This is may be due to the strong electron withdrawing nature of the pyridine ring which made the methylene proton para to it so acidic that it took part in the cyclization. Literature study showed only a few reports to synthesize this kind of fused heterocycle.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Scheme 34, various 6phenylpyrido[2',1' : 2,3]imidazo[4,5-c]quinoline 112 from the reaction of benzyl amines 110 and 2-(imidazo[1,2-a]pyridin-2yl)aniline 111 has been prepared. [93] By utilizing TEMPO as a radical scavenger in the optimized reaction no decrease in yield of desired product was observed, deducing that this mechanism proceeds through non-radical pathway. Mechanistically, role of iodine as catalyst in this approach is oxidative dimerization of benzyl amine 110, to imine precursor A, which then undergoes transamination with 2-(imidazo[1,2-a]pyridin-2-yl)aniline 111 that even acts as a nucleophilic partner for further cyclization.…”
Section: Five-membered Ring Fused With Quinolinesmentioning
confidence: 96%
“…[20] Another approximation consists in the reaction of the corresponding bromide with an aldehyde and an external nitrogen source under copper-catalysis. [21] In addition, the reaction of anilines with benzylamines [22] or 2-methyl azaarenes [23] catalyzed by molecular iodine also led to the formation of imidazo [4,5-c] With this goal in mind, and based on the conditions we had previously reported for the synthesis of pyrrolo and indoloquinoxalines, [10,11d] we found that the treatment of nitroarene 1 a with glycol 2 a (2.2 equiv) in the presence of p-TsOH (0.5 equiv), a catalytic amount of dioxomolybdenum(VI) complex (MoO 2 Cl 2 (dmf) 2 ) and N,N-dimethylacetamide (DMA) as solvent, under microwave heating led to the formation of pyridoimidazoquinoline 3 a (see Table S1), isolated in 70 % yield (Table 1, entry 1). Next, a variety of functionalized glycols 2 were evaluated.…”
Section: Synthesis Of Imidazo[45-c]quinolines 3-6mentioning
confidence: 99%